An investigation into waiting time in public health care facilities in the Capricorn district, Limpopo Province - Mabunda, Gilbert Skhukhuza (My University, 2018)
The purpose of the study was to determine the factors that cause extended waiting time in public health care facilities. The study was conducted in the Capricorn District, Limpopo Province.The study was guided by three objectives:  To describe the average waiting time for patients in public health care centres.  To assess the arrangements in place for outpatients in public health care facilities.  The recommend ways to reduce waiting period. This study is significant because those in authority may use it to formulate and/or improve existing policies and strategies that would contribute in reducing long waiting time. The patients, general public and the Department of Health will be the most beneficiaries of the study. This will culminate in the improvement of healthcare services in public clinics.The population of the study was made up of the total number of clinics in Capricorn District, Limpopo Province. The sample size was 10% of the total population of clinics in Capricorn District. Semi structured questionnaire was used during data collection from sampled health care facilities in Capricorn District. The questionnaire was used as a data collection instrument, where managers of the health care facilities were asked to complete it. The study found that shortage of staff, among other factors, was the main cause behind long waiting time in public health care facilities in the district. The study hereby recommends the recruitment and appointment of sufficient staff in order to reduce waiting time is done sooner than later. This will improve access to health care services which is aligned to the objectives of the National Health Insurance in South Africa and the National Development Plan.
Thesis (MPA.) --University of Limpopo, 2018
Keywords: Public health; Public health -- South Africa